2000
DOI: 10.1016/s0741-5214(00)70064-4
|View full text |Cite
|
Sign up to set email alerts
|

Eversion versus conventional carotid endarterectomy: Late results of a prospective multicenter randomized trial

Abstract: The EVEREST (EVERsion carotid Endarterectomy versus Standard Trial) showed that eversion CEA is safe, effective, and durable. No statistically significant differences were found in late outcome between the eversion and standard techniques at the available follow-up examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
90
1
8

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(108 citation statements)
references
References 40 publications
9
90
1
8
Order By: Relevance
“…However, standard CEA with patch angioplasty had the lowest incidence of neurologic events. Both differences were not statistically significant [13]. Two years later, authors of EVERST study concluded that reduced restenosis after eversion CEA, did not appear to be associated with clinical benefit in terms of reduced stroke risk, either preoperatively or later [14].…”
Section: Reviewmentioning
confidence: 91%
See 3 more Smart Citations
“…However, standard CEA with patch angioplasty had the lowest incidence of neurologic events. Both differences were not statistically significant [13]. Two years later, authors of EVERST study concluded that reduced restenosis after eversion CEA, did not appear to be associated with clinical benefit in terms of reduced stroke risk, either preoperatively or later [14].…”
Section: Reviewmentioning
confidence: 91%
“…Numerous studies have compared standard CEA plus patching with eversion once [7][8][9][10][11][12][13][14][15][16][17][18]. Regarding the total operating and ischemic time, as well as perioperative complications, first studies has favored to eversion CEA [7,8].…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Most surgeons do open carotid endarterectomy but some prefer the eversion endarterectomy technique. A couple of randomized trials, including the EVEREST study, suggested that the eversion endarterectomy method carries equivalent or lower death and stroke rates 14,15 . However, the technique is not suitable for all patients and a carotid shunt is not easily inserted during the procedure.…”
Section: Operative Techniquementioning
confidence: 99%